The Gendered Toy Choice (GTC): validating a behavioral measure of gendered parenting - Kislev, Noya; Saguy, Tamar (Frontiers in Psychology, 2025)
Gendered parenting reflects parents' tendency to promote gender-typed behaviors of their children, shaping their everyday experiences and environments. Existing research primarily relies on self-report or observational methods, limiting behavioral insights. This study introduces the development and validation of the Gender Toy Choice (GTC) measure, an unobtrusive behavioral tool assessing parents' real-time product choices for their children. In three studies conducted among Israeli and U.S. parents to preschool children, the GTC measure demonstrated face, construct, concurrent, convergent, and discriminant validity, supporting its theoretical relevance. Findings highlight how parental choices reinforce gender norms in children's daily lives and provide a standardized behavioral measure for future research. By offering a novel, easy-to-implement tool, this work contributes to the study of factors underlying parents' gendered decision-making and the mechanisms shaping gendered parenting practices.